EFEK EKSTRAK AKAR GINSENG JAWA DAN KOREA TERHADAP LIBIDO MENCIT JANTAN PADA PRAKONDISI TESTOSTERON RENDAH - Dwi Winarni (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2007)
This research was designed to compare the potency and duration effect of Java ginseng and Korean ginseng root extract administration on sexual behavior of male mice. It was done experimentally on male mice (strain BALB, aged 8–10 weeks, weighed 25–35 g). Thirty eight mice were grouped to 4 (four) groups: First group was treated with solvent (as positive control), 2nd group was treated ethynilestradiol (EE2) (as negative control), 3rd group was treated with Java ginseng root extract, and 4th group was treated with Korean ginseng root extract. All groups were administered with EE2 0.56 mg/20 g bw/day for 9 days as pretreatment to decrease the testosteron level. After pretreatment, each group divided to 3 subgroups (each would receive treatment for 9, 18, and 27 days). Ethynilestradiol 0.56 mg/20 g bw/day was administered along treatment to keep testosterone level low, except to positive control group. Java ginseng and Korean ginseng root extract (equal with 1.4 mg ginseng root powder/ 20 g bw/day) and EE2 were administered orally. The level of testosterone after pretreatment was measured by RIA (radioimmuoassay) and changes in libido were determined by libido test. After the last treatment, 1 male mouse kept singly in individual cage. Libido test was carried out for 20 minutes. All of these activities during test recorded by handycam. The mice were observed for time from the introduction of female into the cage of male upto the first mount (mounting latency/ ML) and for the number of mounts (mounting frequency/MF). The results indicated that at low testosterone level, Java ginseng root extract administration at the dose equal with 1.4 mg ginseng root powder/20 g bw/day shortened mounting latency and increased mounting frequency but Korean ginseng extract root at the same dose gave negative effects. Duration of administration of both Java and Korean ginseng root extract didn’t give effect on libido.